REPRODUCTIVE PERFORMANCE OF MORADA NOVA EWE SUBJECTED TO ESTRUS INDUCTION BY MALE EFFECT (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
This study aimed to evaluate the reproductive performance of crossbred sheep (New Address) nulliparous, primiparous and pluriparous, subjected or not to the male effect. There were used 79 ewes and two rams (one vasectomised ram – teaser ram) and a breeder). In the first year, the females were subjected to the male effect (ME: male effect), in the following year, there has been no application of this method (AME: absence of male effect). Ewes subjected to ME showed a higher synchronization (P